Factors contributing to increased Neonatal Mortality in Grand Kru County, Liberia, January 2017-December 2021 - Jimmy Lawubah; Chukwuma David Umeokonkwo; Himiede Wede Sesay; Babalola Joseph Obafemi; Faith Tina Whesseh; Leroy Maximore; Francis Bobway; Boye Nuyelleh; Lily Marie Sanvee-Blebo; Maame Amo-Addae (Journal of Interventional Epidemiology and Public Health)
Introduction: The average global neonatal mortality rate is 17 deaths per 1,000 live births, while in Liberia, the neonatal mortality rate is 30.6 deaths per 1,000 live births as of 2020. Liberia is among the countries in the world with the highest neonatal mortality rate. In 2016, the former president of Liberia declared neonatal mortality as a public health emergency due to the high neonatal mortality rate which was recorded as 42 deaths per 1,000 live births. Grand Kru County is one of the counties in Liberia where neonatal death is reported nearly every month. The aim of this study is to describe the burden of neonatal death in Grand Kru from 2017-2021 and identify direct causes and contributory factors.